Ultra-wideband optically transparent flexible metamaterial absorber for satellite stealth - Chao Zhao; Min Jia; Ningtao Zhang; Shiyao Meng; Yanhong Tian (Scientific Reports)
Abstract With the rapid advancement of space technology, the stealth capabilities of satellites have become crucial for enhancing their survivability and increasing mission success rates. However, traditional absorbing materials do not adequately address the requirements for flexible conformal designs, high transmittance in the visible light spectrum, and ultra-wideband absorption capabilities in microwave frequencies. To address this issue, we developed an ultra-thin, flexible, ultra-wideband metamaterial absorber that is optically transparent and insensitive to polarization and angle. This design is based on indium tin oxide (ITO) material. The results of the electromagnetic simulation indicate that within the frequency range of 11.09 GHz to 108.20 GHz, the absorption rate of the absorber exceeds 90%. The total absorption bandwidth is measured at 97.11 GHz, resulting in a relative absorption bandwidth of 162.81%. In addition, it continues to demonstrate effective absorption performance for electromagnetic waves with an incident angle of less than 45°. The absorber designed in this study exhibits polarization-insensitive characteristics, enabling it to effectively address the detection of multi-polarization radar. Furthermore, it is compatible with the arbitrary deployment attitudes of the carrier, which significantly enhances the operational reliability of the stealth system in actual combat scenarios.